ANALYSIS OF FINANCIAL STATEMENT IN ASSESSING THE FINANCIAL PERFORMANCE OF LOCAL GOVERNMENT - Helda Aslim Safitry; Dwi Iga Luhsasi; Carolina Lita Permatasari (JRAK, 2021)
The financial statement can be used to determine company activities, one of them to assess the condition of financial to balance and profit /loss statement. For asses and analyze financial statements are required analysis tools are financial rations. The purpose of this study is to determine the financial performance of the Wiru Village government in 2018-2020. This study uses a qualitative approach with financial analysis tools. The result of this study is Wiru village in 2018- 2020 the self-reliance ratio is very low, effectiveness ratio is very effective, in 2018 the efficiency ratio is not efficient and in 2019-2020 is not efficient, the dependency ratio is very high, and the growth ratio in 2018-2019 has decreased, and then in 2019- 2020, it has increased.